Iterates of Volterra operators and indeterminate forms - Pablo Braz e Silva; Andrés R. R. Papa (International Journal of Mathematics and Mathematical Sciences)
We state and prove a theorem showing how iterates of the Volterra operator can be used to evaluate indeterminate forms of type 0/0. This general result allows one to recover the Boltzmann-Gibbs entropy as a limit of a wide class of generalized entropies, as considered in an earlier work.